Simplified multi-step predictive control for surface permanent magnet synchronous motor. (December 2020) - Li, Yaohua; Su, Jinshi; Qin, Hui; Zhao, Chenghui
Abstract: Aiming at reducing computational complexity in the multi-step model predictive torque control (MPTC), a novel simplified multi-step MPTC algorithm (P-MPTC) was proposed. Firstly, a multi-step MPTC model was established, and the computational burden of the traditional MPTC (T-MPTC) was discussed. Secondly, based on the MPTC with simplified voltage set (S-MPTC), a simplified MPTC with voltage holding approach (P-MPTC) was proposed, which avoided enumerating all the voltage vectors in candidate set to simplify the computation. Finally, the proposed MPTC algorithm was compared with T-MPTC and S-MPTC to analyze the differences of control performance and computational burden. The result shows that, the proposed simplified algorithm can greatly reduce the computational complexity of multi-step MPTC while the control performance almost not change. For example, in the six-step MPTC, the computational burden in the proposed simplified algorithm is only 0.02% of that in the traditional algorithm, which verifies the effectiveness of the proposed algorithm.